Bone-spicule pattern in retinitis pigmentosa - Krzysztof Eder; Rafał Leszczyński; Ewa Mrukwa-Kominek; Paulina Langosz; Sebastian Sirek (Klinika Oczna)
Bone spicules constitute one element of the triad of characteristic symptoms found in the eye fundus of patients with retinitis pigmentosa. More than 70 genes are linked to retinitis pigmentosa through mutations. However, the disease may not always show symptoms or can present in ways that deviate from the classic clinical picture. The occurrence of the disease is not due to damage in a single metabolic pathway. Rather, it is a multifactorial pathophysiological process involving the failure of various cellular regulatory mechanisms and the presence of histopathological changes. The macroscopic image of the fundus is a result of the migration of cells from damaged retinal pigment epithelium, which is additionally characterized by abnormalities at the cytological level. The specific taxic factors triggering the distinct pattern of cell migration in this disease remain unclear. Based on the available literature there is no direct correlation between the presence of bone spicules in the eye fundus and the decline in visual acuity associated with retinitis pigmentosa.